KETENTUAN PERKAWINAN MENURUT UNDANG-UNDANG PERKAWINAN DAN FIKIH MUNAKAHAT - Saputra, Dwi Arya; Indra, Muhammad; Harianto, Muhammad Indra Lukman; Karima, Gusti Najwa; Afifa, Shulha (Program Studi Hukum Keluarga Islam, Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
This study discusses the provisions on the age of marriage from the perspective of Islamic law and Indonesian positive law, highlighting the conceptual differences between Fikih Munakahat and Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974. In Islamic law, the age limit for marriage is not determined numerically, but is based on signs of puberty and a person's physical, mental, and moral readiness. In contrast, positive law sets a minimum age of 19 for men and women as a form of protection for children and an effort to create prosperous and responsible families. This study uses a normative legal research method with a legislative and conceptual approach, through a literature review of primary and secondary legal sources. The results show that although there is no fundamental difference in the objectives of the two legal systems, normative tension still exists at the practical level due to the difference in emphasis between the flexibility of Islamic law and the strictness of positive law. Therefore, the setting of age limits by the state can be seen as a form of contemporary ijtihad in line with the principle of maqāṣid al-sharī‘ah to maintain public interest, protect the younger generation, and prevent underage marriage.